High precision positioning algorithm based on carrier phase and time of arrival - Zhenyu Zhang (Wiley, 2021)
Abstract Carrier phase positioning technology is widely used in global navigation satellite systems (GNSS) but not applied to wireless orthogonal frequency division multiplex (OFDM) systems. Carrier phase technology has a high resolution, which can improve the positioning accuracy of wireless cellular networks. Applying the carrier phase to a wireless mobile positioning system has some problems, such as continuous phase tracking, accurate integer ambiguity resolution, positioning errors caused by non‐line‐of‐sight (NLOS) and so forth. This paper offers a positioning technique combining the time‐of‐arrival (TOA) and carrier phase to solve the above problems. Based on Bayesian theory, a two‐step position estimator is introduced in our scheme to solve the terminal position. Besides, an NLOS identification and suppression scheme is proposed to enhance the robustness of the algorithm. Experiments show that even in the NLOS environment, the joint positioning algorithm using TOA and carrier phase can effectively improve the positioning accuracy.